Nonlinear quasi-static finite element simulations predict in vitro strength of human proximal femora assessed in a dynamic sideways fall setup. (April 2016) - Varga, Peter; Schwiedrzik, Jakob; Zysset, Philippe K.; Fliri-Hofmann, Ladina; Widmer, Daniel; Gueorguiev, Boyko; Blauth, Michael; Windolf, Markus
Abstract: Osteoporotic proximal femur fractures are caused by low energy trauma, typically when falling on the hip from standing height. Finite element simulations, widely used to predict the fracture load of femora in fall, usually include neither mass-related inertial effects, nor the viscous part of bone׳s material behavior. The aim of this study was to elucidate if quasi-static non-linear homogenized finite element analyses can predict in vitro mechanical properties of proximal femora assessed in dynamic drop tower experiments. The case-specific numerical models of 13 femora predicted the strength ( R 2 =0.84, SEE=540 N, 16.2%), stiffness ( R 2 =0.82, SEE=233 N/mm, 18.0%) and fracture energy ( R 2 =0.72, SEE=3.85 J, 39.6%); and provided fair qualitative matches with the fracture patterns. The influence of material anisotropy was negligible for all predictions. These results suggest that quasi-static homogenized finite element analysis may be used to predict mechanical properties of proximal femora in the dynamic sideways fall situation. Graphical abstract: Highlights: Proximal femur fracture was induced in drop tower tests mimicking fall ( N =14). Homogenized finite element (hFE) models were generated automatically from CT images. Quasi-static hFE analysis predicted hip fractures occurring in dynamic sideways fall. Strength ( R 2 =0.84), stiffness ( R 2 =0.82) and fracture energy ( R 2 =0.72) were predicted.